Sentencing Add-Ons and Implications for Disparities in a Guidelines State - Strange, C. Clare (Crime & delinquency, 2022)
This study examined whether and how discretionary sentencing add-ons (i.e., secondary charges, victim injury points, firearms/weapons points, drug trafficking enhancements) contribute to disparities. We examined add-ons that increase sentencing points and so contribute to a defendant ?scoring to prison.? We analyzed: (1) the degree to which add-ons explain racial and ethnic disparities in imprisonment (mediation); and (2) whether add-ons are more adverse for minority defendants (moderation). We did not find that add-ons ?explain? racial differences in the use of prison sentences. We did find, however, that some add-ons, particularly those that signal ?dangerousness,? are racially/ethnically disparate in their consequences. The findings raise questions about the role of court discretion in perpetuating racial and ethnic disparities.